Merkel cell carcinoma – description of five cases - Brąclik, Mariusz; Kwiatkowski, Robert; Nenko, Dorota Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2013)
Merkel cell carcinoma (MCC) is a rare but very aggressive skin cancer that derives from neuroendocrine cells of the skin. Merkel cell carcinoma morbidity has been continuously increasing for the last few years. Increasing reported incidence of MCC is probably connected with increasing occurrence of this kind of malignancy or with development of histological and immunohistochemical methods of sample examinations which have allowed for more precise diagnosis of skin tumor that might have previously not been accurately recognized. Merkel cell carcinoma develops as nodules early recognized as basocellular carcinoma, squamous cell carcinoma, amelanotic melanoma or skin lymphoma. Merkel cell carcinoma can be morphologically similar to skin metastasis as well as mild changes such as lipoma, cysts, fibroma or vessel changes. Accurate diagnosis is very important because it determines successful management and risk of progression of disease. We describe 5 patients with MCC who underwent surgical excision and then, after estimation of stage of disease, complementary treatment. Our observations prove that every tumor with MCC should be cut out with wide margins and regional lymphadenectomy or sentinel node biopsy is compulsory. After cutting out MCC involved-field radiotherapy is necessary and improves prognosis. Presence of metastases in lymphatic nodes is an indication for complementary chemotherapy.